Manuela D’Amore, Literary Voices of the Italian Diaspora in Britain. Time, Transnational Identities and Hybridity (Altre Modernità, 2024)
“wrong that you should go  into a strange world so soon.” Voci in inglese dell’immigrazione italiana  (Manuela D’Amore, Literary Voices of the Italian Diaspora in Britain. Time, Transnational Identities and Hybridity, London, Palgrave Macmillan, 2023, 328 pp. ISBN 9783031354373)  di Paolo Caponi